MODEL PEMBELAJARAN DAN PRINSIP BERMAIN PENCAK SILAT UNTUK ANAK PRASEKOLAH - Erwin Setyo Kriswanto (Jurnal Pendidikan Jasmani Indonesia, 2008)
The appropriate learning process for preschool children is by playing. Playing is inconsciously part of basic movement of pencak silat such as kicking, punching, eluding, or running. Not all of basic movements in pencak silat are appropriate for preschool children. Teachers need to be careful in selecting or defining appropriate technique and movement. In delivering basic movements of pencak silat for preschool children needs to include playing methods and develops socialization aspects including the use of language/ terminology modified in order not to have violent impression. Children do not need to be introduced about the concept of enemy, because the main aspect for them is to grow. Because growing them needs stumulations so pencak silat is only for fun, sport and discipline development, bot for sefl-defense. In other words, it needs to consider learning principals for preschool children. Leaning pencak silat using playing methods can be done by playing model, story telling, dancing, immitating movement, or demonstrating something. Kata kunci: Model pembelajaran, Prinsip bermain, Pencak silat, Usia prasekolah